Active filter for harmonic and reactive power compensator / Abdul Manap Hanafi - Hanafi, Abdul Manap (1996)
In recent years there has been an increasing concern over the introduction of current harmonics in power supply system owing to the use of non linear loads. Conventional filtering techniques which use passive fitters are inflexible because they cannot cope with variation in the filtering requirements as the load and system conditions vary. The development of an active filter that can be connected across a non-linear load, is capable of self-tuning and overcomes the disadvantages of the conventional passive filters, is presented .In this technique, the utility is required to supply only the fundamental component of current required by the load; leading to a harmonic - free system. This current injected active filter was successfully implemented and tested.